2020
DOI: 10.1007/s12325-020-01236-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravitreal Aflibercept Treat-and-Extend Regimens in Exudative Age-Related Macular Degeneration: 52- and 96-Week Findings from ALTAIR

Abstract: Purpose: To evaluate efficacy and safety of intravitreal injections of aflibercept (IVT-AFL) treat-and-extend (T&E) dosing regimens in treatment-naïve patients with exudative agerelated macular degeneration (AMD).Methods: Adults aged at least 50 years old with exudative AMD and best-corrected visual acuity (BCVA) of 73-25 Early Treatment Diabetic Retinopathy Study (ETDRS) letters were included. Patients received three monthly doses of IVT-AFL 2 mg. At week 16, patients were randomized 1:1 to IVT-AFL T&E with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
219
1
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(246 citation statements)
references
References 23 publications
18
219
1
8
Order By: Relevance
“…In contrast, TAE uses a shortened injection interval when exudative changes remain or worsen and an extended injection interval when exudative changes disappear [14][15][16][17][18][19]. In the current study, the administration interval was extended by 2 weeks when the exudative changes disappeared after at least three monthly loading treatments, with administrations reset to the initial 1-month interval after any recurrence.…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, TAE uses a shortened injection interval when exudative changes remain or worsen and an extended injection interval when exudative changes disappear [14][15][16][17][18][19]. In the current study, the administration interval was extended by 2 weeks when the exudative changes disappeared after at least three monthly loading treatments, with administrations reset to the initial 1-month interval after any recurrence.…”
Section: Introductionmentioning
confidence: 85%
“…Of note, the randomized Phase 4 ALTAIR trial demonstrated a last intravitreal aflibercept injection interval of at least 12 weeks with a 2 or 4 week treat-and-extend (TREX) strategy in 57% and 60% of treatment-naive patients with nAMD by week 96. 29 The randomized Phase 3 trials of HAWK and HARRIER demonstrated that approximately 50% of patients with untreated, active nAMD can be maintained on 12 week interval treatments of intravitreal brolucizumab without rescue therapy. 30 From clinical practice and published data, the q12 week injection intervals for aflibercept and brolucizumab are the longest demonstrated efficacious duration of the currently available medications.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there remain unmet needs for the treatment of these conditions. The current pharmacologic agents are indicated for repeated intravitreal (IVT) injections every 1-3 months [6][7][8], although less often retreatment has shown to be effective [10][11][12][13][14][15]. This significant treatment burden is unsustainable, and many patients receive fewer than the recommended number of injections with commensurately suboptimal visual outcomes [16][17][18][19][20][21].…”
Section: Areas Coveredmentioning
confidence: 99%